Analisis Yuridis‑Sosiologis Putusan Nomor 256/Pdt.G/2025/PA.Smn - Ramadhan, Gilang; Ambarwati, Mega Dewi (Media Hukum Indonesia (MHI), 2025)
This article critically examines the Decision of the Sleman Religious Court Number 256/Pdt.G/2025/PA.Smn which granted the wife's divorce suit with the order of talaksatu baʾin sughra. The focus of the study includes the legitimacy of the reasons for divorce, the relevance of evidence, the application of civil procedural law (verstek), and its implications for the protection of the rights of Muslim women in Indonesia. The methodology used is normative-sociological legal research with a statutory approach, decisions, and fiqh literature. The results show: (1) the arguments of continuous disputes, non-maintenance, and desertion fulfill Article 19 letter (f) of PP9/1975 in conjunction with Article 116 letter (f) of the KHI; (2) the combination of written evidence and two consistent witnesses strengthens the basis for justifying the lawsuit; (3) the verstek mechanism still guarantees due process as long as the summons is valid; (4) This decision provides a positive precedent for wives affected by unfair power relations in the household. Recommendations are submitted for the Supreme Court to strengthen technical guidelines on proof of desertion and for related ministries to increase gender equality-based family law literacy.